The factors associated with prevalence of Hepatitis B vaccination among practicing dentists in Manila - Oliva, Anna Lorraine Q.; Reyes, Leigh Rochelle C.; Sia, May Carol M. (Co-Author).
In the Philippines, one of the occupational hazards that the average dentist faces everyday is the possibility of infection or cross infection with Hepatitis B. Already tagged by the World Health Organization (WHO) as one of the countries where Hepatitis B is highly endemic and more than 8% of the population carries the virus, the advent of Hepatitis B vaccination was thought to decrease the incidence of Hepatitis B morbidity, However, despite the apparent safety of these vaccines, some dentists do not see the necessity of this vaccine citing its costs and lack of information regarding the vaccine as reasons for refusing, ft is the purpose of this study to determine the factors that affect the dentist's willingness to have themselves vaccinated against the infectious disease, It is also the aim of this study to determine whether a dentist's vaccination status affects his willingness to treat Hepatitis B infected patients. Survey questionnaires were distributed using convenience sampling to 125 respondents. Data collected were analyzed using Pearson's test, Chi-square test and Paired Correlations Sample. The results showed that there was no significant correlation between the prevalence of Hepatitis B vaccination among practicing dentists in Manila and the following factors; (1) Type of Practice; (2) Number of Years in Practice; (3) Degree of Knowledge Regarding Hepatitis B Vaccination and Infection. There was also no significant relation between a dentist's vaccination status and his willingness to treat Hepatitis B infected patients.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Hepatitis B Vaccines; Dentists -- Risk management; Dentistry -- Safey measures